Evaluation of the educational level and its influence on the success rate of complete denture - KEERTHANA, R.; DURAISAMY, REVATHI; CHAUDHARY, MANJARI (The journal of contemporary issues in business and government, 2021)
Except for denture quality, many other factors are related to a patient’s satisfaction with complete dentures (CDS). Complete denture construction provides dentures that have a pleasing appearance, maintain normal speech, provide occlusal support and supply adequate means for the mastication of food. In addition to this dentures should be comfortable and contribute to the continuing health of the supporting tissues. The aim of the study was to find if and how the educational level of the patient influenced the success rate of complete denture delivered in Saveetha Dental College. A survey was conducted among 119 patients who had received complete dentures from Saveetha Dental College Questionnaire on the educational level and the quality of their denture was asked. The data was retrieved from 86,000 patients among which 119 complete denture denture patients were selected. The results were tabulated, Descriptive statistics, cross tabulation and chi-square test was done by SPSS IBM software 20.0 The most common educational qualification of the patient was higher (33%). It was found that a better satisfactory level was found in high educational qualification patients p>0.001. Level of education, self perception of affectivity are all related to patient satisfaction. Within the limits of the study it was found that patients with higher educational level had more satisfaction of the denture than the patients with low educational qualification.